Allogeneic Umbilical Cord Blood–Derived Mesenchymal Stem Cell Implantation Versus Microfracture for Large, Full-Thickness Cartilage Defects in Older Patients: A Multicenter Randomized Clinical Trial and Extended 5-Year Clinical Follow-up. Issue 1 (12th January 2021) - Lim, Hong-Chul; Park, Yong-Beom; Ha, Chul-Won; Cole, Brian J.; Lee, Beom-Koo; Jeong, Hwa-Jae; Kim, Myung-Ku; Bin, Seong-Il; Choi, Chong-Hyuk; Choi, Choong Hyeok; Yoo, Jae-Doo; ,; et al.
Background: There is currently no optimal method for cartilage restoration in large, full-thickness cartilage defects in older patients. Purpose: To determine whether implantation of a composite of allogeneic umbilical cord blood–derived mesenchymal stem cells and 4% hyaluronate (UCB-MSC-HA) will result in reliable cartilage restoration in patients with large, full-thickness cartilage defects and whether any clinical improvements can be maintained up to 5 years postoperatively. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: A randomized controlled phase 3 clinical trial was conducted for 48 weeks, and the participants then underwent extended 5-year observational follow-up. Enrolled were patients with large, full-thickness cartilage defects (International Cartilage Repair Society [ICRS] grade 4) in a single compartment of the knee joint, as confirmed by arthroscopy. The defect was treated either with UCB-MSC-HA implantation through mini-arthrotomy or with microfracture. The primary outcome was proportion of participants who improved by ≥1 grade on the ICRS Macroscopic Cartilage Repair Assessment (blinded evaluation) at 48-week arthroscopy. Secondary outcomes included histologic assessment; changes in pain visual analog scale (VAS) score, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and International Knee Documentation Committee (IKDC) score from baseline; and adverse events. Results: Among 114 randomized participants (mean age, 55.9 years; 67% female; body mass index, 26.2 kg/m 2 ), 89 completed the phase 3 clinical trial and 73 were enrolled in the 5-year follow-up study. The mean defect size was 4.9 cm 2 in the UCB-MSC-HA group and 4.0 cm 2 in the microfracture group ( P = .051). At 48 weeks, improvement by ≥1 ICRS grade was seen in 97.7% of the UCB-MSC-HA group versus 71.7% of the microfracture group ( P = .001); the overall histologic assessment score was also superior in the UCB-MSC-HA group ( P = .036). Improvement in VAS pain, WOMAC, and IKDC scores were not significantly different between the groups at 48 weeks, however the clinical results were significantly better in the UCB-MSC-HA group at 3- to 5-year follow-up ( P < .05). There were no differences between the groups in adverse events. Conclusion: In older patients with symptomatic, large, full-thickness cartilage defects with or without osteoarthritis, UCB-MSC-HA implantation resulted in improved cartilage grade at second-look arthroscopy and provided more improvement in pain and function up to 5 years compared with microfracture. Registration: NCT01041001, NCT01626677 (ClinicalTrials.gov identifier).